2018
DOI: 10.4110/in.2018.18.e30
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Specific Knockout of STAT3 Ameliorates Dextran Sulfate Sodium-Induced Colitis by Reducing the Inflammatory Response

Abstract: Signal transducer and activator of transcription 3 (STAT3) has a crucial role in various autoimmune disorders including, inflammatory bowel disease (IBD). Our previous study demonstrated that STAT3 activation by IL-6 in colonic epithelial cells exacerbates experimental ulcerative colitis. Activated T lymphocytes are also found in ulcerative colitis patients with intestinal inflammation, but the role of STAT3 in T cells remains elusive. To determine the STAT3 function of T cells in intestinal inflammation, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
2
10
0
1
Order By: Relevance
“…Treatment with BDS suspension, KO liposomes, or BDS-entrapped KO liposomes slightly decreased the DSS-induced level of DAI, although statistically not significant (Figure 6A). The colon length was shortened in DSS group, in accordance with the findings of other studies 29,30. BDS or KO liposome treatment slightly but significantly ameliorated DSS-induced colon shortening (Figure 6B).…”
Section: Resultssupporting
confidence: 91%
“…Treatment with BDS suspension, KO liposomes, or BDS-entrapped KO liposomes slightly decreased the DSS-induced level of DAI, although statistically not significant (Figure 6A). The colon length was shortened in DSS group, in accordance with the findings of other studies 29,30. BDS or KO liposome treatment slightly but significantly ameliorated DSS-induced colon shortening (Figure 6B).…”
Section: Resultssupporting
confidence: 91%
“…IL-6 augments the expression of STAT3 in the colon, thereafter, regulates the polarization of IEC (Serrano et al, 2019). T cell-specific knockout of STAT3 ameliorates DSS-induced colitis by reducing the inflammatory response (Kwon et al, 2018). In our study, we uncovered that DSS induces the upregulation of STAT3 in the colon along with other inflammatory cytokines including IL-6.…”
Section: Discussionmentioning
confidence: 53%
“…In animal model, we found that LXN deficiency leads to severity of DSS colitis, which can be demonstrated by a number of clinicopathological indicators, including more severe weight loss, hematochezia, shortening of the colon and rectum, damage to the mucosa and loss of goblet cells, increased proinflammatory cytokines and increased STAT3 activity. Many literatures have reported the key role of JAK/STAT3 signal transduction pathway in the pathogenesis of IBD [33][34][35][36] . In the cell model, we prove that ectopic expression of LXN inhibits both basal and TNF-α-induced NF-κB-Luc activity.…”
Section: Discussionmentioning
confidence: 99%